THE INFLUENCE OF WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION IN THE BANKING INDUSTRY - Anak Agung Dwi Marsita Anggraeni; I Gede Riana (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to examine the influence of work-life balance (WLB) on job satisfaction and employee performance, as well as the mediating role of job satisfaction in this relationship. The sample consisted of 135 employees selected using probability sampling in the banking industry in Badung Regency. Data were collected through a questionnaire and analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS 3.0. The findings reveal that WLB has a positive and significant effect on both job satisfaction and employee performance. Job satisfaction also has a significant positive effect on performance. Furthermore, job satisfaction partially mediates the effect of WLB on performance, supporting the framework of Social Exchange Theory, which emphasizes the importance of reciprocity in the employee-employer relationship. The practical implications highlight the importance of implementing WLB strategies to foster a healthy and productive work environment. Organizations are encouraged to develop flexible work policies and enhance job satisfaction to improve sustainable employee performance. Future research is recommended to broaden the scope across sectors and employ varied methodological approaches to deepen the understanding of the interrelationships among the studied variables.